Perceptrón basado en Kernel para reconocimiento de dígitos manuscritos - Rojas Galeano, Sergio Andrés (Ingeniería, 2003)
Kernel-based learning machines have been proposed as a new approach to use neural networks architectures applied to non-linear classification and recognition problems with many good results reported recently. In this paper we describe the implementation of a perceptron neural network for classification of real digit number data set, based on the kernel learning method. The classifier obtains a successful recognition score near to 93% on unseen patterns.